Pemberdayaan Kreativitas Petani Aren Melalui Pelatihan Pembuatan Nata de Legen Di Desa Sidokaton, Kecamatan Gisting, Kabupaten Tanggamus, Lampung - Endang Nurcahyani; Hendri Busman; Yulianty (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Communities have long recognized the sugar palm (Arenga pinnata Merr.) as a plant that produces various economically valuable products, particularly for the craft and food industries; however, its development and cultivation have received relatively little attention. In Sidokaton Village, Gisting District, Tanggamus Regency, the sugar palm is one of the leading local commodities widely cultivated by farmers. Most farmers process sugar palm into palm sugar and kolang-kaling, while the sap is commonly used only as a fresh beverage with a low selling price that fluctuates significantly during the harvest season. This condition highlights the need for innovations in utilizing sugar palm sap to increase its added value for farmers. This community service activity introduces an innovation in processing sugar palm sap into Nata de Legen as an alternative to nata de coco. This innovation aims to enhance the community’s knowledge and skills regarding product diversification of sugar palm and to encourage increased income through higher-value processed products. There was an increase in public knowledge about processing and utilizing palm sap to produce the economically valuable nata de legen. The average increase in knowledge among training participants was 17.33 points. The training activities are expected to serve as an initial step in the development of sustainable local resource–based enterprises in Sidokaton Village.